Strategi Optimalisasi Outlet Bank Negara Indonesia Pemutus Kredit Konsumer Pada Kantor Wilayah Makassar - Sudirman NS; Otto R Payangan; Musran Munizu (Magister Management, Hasanuddin University, 2019)
This study aims to identify (a) the factors that influence the optimization of Bank Negara Indonesia outlets for consumer credit breakers at the Makassar Regional Office; and (b) identify the strategies used by BNI SKK Makassar Branch of Peer Control as a consumer credit breaker outlet. This research is a type of exploratory research by identifying and developing a strategy for optimizing consumer credit breakers. Research location at Bank BNI SKK Branch Mattoangin Peer Makassar. Data collected includes primary data and secondary data. Primary data was collected through in-depth interviews and distributing questionnaires (questionnaires) to 17 informants. Secondary data in the form of financial statements, and bank performance reports. The population and sample in this study are all leaders and employees, so the sample in this study is a saturated sample. Data analysis uses internal and external environmental analysis, TOWS analysis and General Electric. The results of the study show that internal factors (strength) that support the BNI Branch of Mattoangin as credit breakers are absorbing new business potential, adequate human resources, distributing Mattoangin branch outlets that are evenly distributed, increasing deposits, and improving HR knowledge. External factors (opportunities), namely the potential of new business, cooperation with business people, and a holistic understanding of business. An alternative strategy for BNI Branch Mattoangin as a consumer credit breaker in the form of increasing mortgage loans that focuses on the potential consumer credit segment, strategies to increase cooperation with housing developers who have extensive networks, strategies to increase CASA and growth in demand deposits.